our financial action plan : - Cunningham, G. Cotter. (John Wiley & Sons, 2004)
With this book as your guide, you’ll learn how to: * Make the most of your mortgage * Maintain a good credit rating * Build your retirement savings * Negotiate with your local bank to get the best deals * Navigate the ins and outs of insurance * Create a will * Handle tax deductions and credits * And much more